2013
DOI: 10.5012/bkcs.2013.34.7.2029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phosphorous-doping on Electrochemical Performance and Surface Chemistry of Soft Carbon Electrodes

Abstract: The impact of phosphorous (P)-doping on the electrochemical performance and surface chemistry of soft carbon is investigated by means of galvanostatic cycling and ex situ X-ray photoelectron spectroscopy (XPS). P-doping plays an important role in storing more Li ions and discernibly improves reversible capacity. However, the discharge capacity retention of P-doped soft carbon electrodes deteriorated at 60 o C compared to non-doped soft carbon. This poor capacity retention could be improved by vinylene carbonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…Even three minutes of sputtering made the O1s signal disappear completely, which is not surprising given that SEIs on basal planes are known to be significantly thinner than on edge planes ,. The peak positions in Figure are in good agreement with features in previous XPS analyses of SEI layers …”
Section: Resultssupporting
confidence: 84%
“…Even three minutes of sputtering made the O1s signal disappear completely, which is not surprising given that SEIs on basal planes are known to be significantly thinner than on edge planes ,. The peak positions in Figure are in good agreement with features in previous XPS analyses of SEI layers …”
Section: Resultssupporting
confidence: 84%
“…NPC (with a P concentration of 0.84at% and a N concentration of 8.85at%) delivers higher conductivity in comparison with NSC (with a S concentration of 0.80at% and a N concentration of 10.78at%), indicating that the P doping contributes a larger enhancement to the electronic conductivity of the as prepared soft carbon than S doping does. Previously theoretical calculations have demonstrated that P and/or S doping is able to improve the electron-donor properties of carbon materials, conclusively accompanied by an increased conductivity, and this is consistent with our results[25,38].…”
supporting
confidence: 93%
“…With the doping of S atoms, the peak position of P-O shifts to lower binding energy, and another new peak appears at 133.8 eV, indicating the presence of P-S bonds [36]. As reported, theoretical calculations show that P-doping in carbon induces the negatively delocalization of C atoms adjacent to P atoms, due to the fact of lower electronegativity of P (2.19) than that of C (2.55) and thus results in a negative charge around the carbon atoms which can reinforce the adsorption interaction with Li + [37,38]. The S 2p peak is split into two peaks at 164.5 and 168.6 eV, corresponding to the binding energies of sulphide (C-S-C/S-P) and sulphone (C-SOx-C), respectively.…”
Section: Resultsmentioning
confidence: 57%
“…Increases in the charge and discharge capacities upon P-doping of coke were reported [223]. The increase of the reversible capacity of carbon with P-doping was ascribed to an increase in the number of sites accepting Li ions and an increased interlayer spacing allowing facile Li intercalation.…”
Section: Li-ion Batteriesmentioning
confidence: 97%
“…phosphoric acid [217][218][219][220][221][222][223][224][225][226][227][228], H 3 PO 4 without heating [229], ultrasonic-assisted anodic treatment with H 3 PO 4 [230], treatment with phosphate and phosphite esters [231], methylphosphonic acid [20,232,233], PCl 3 [234][235][236][237], POCl 3 [20,233,238], triphenylphosphine [239][240][241], phytic acid [242],…”
Section: 2mentioning
confidence: 99%